Family functioning and post-traumatic growth among disaster survivors: The mediation role of hope - Setiawan, Intan Masruroh; Diana Setiyawati (Humanitas: Indonesian Psychological Journal, 2025)
Post-traumatic growth enables disaster survivors to continue functioning in their post-disaster lives optimally, and enables them to be better equipped to face difficulties in the future. This research aims to test the role of hope in mediating the relationship between family functioning and post-traumatic growth in survivors of the Mount Semeru eruption disaster. The participants in this research were 180 people aged 18-60 years who were survivors of the Mount Semeru eruption disaster in 2021. The instruments used were the Post-traumatic Growth Inventory-Expanded (PTGI-X), Family Adaptability and Cohesion Evaluation Scale IV (FACES-IV), and Adult Hope Scale (AHS). Simple mediation analysis was used to analyze the data. The results show that hope partially mediates the relationship between family functioning and post-traumatic growth in survivors of the Mount Semeru eruption disaster. It means that family functioning can influence post-traumatic growth directly and indirectly through hope as a mediator. This finding can provide input for stakeholders regarding the development of holistic interventions for disaster survivors, both at the individual level related to their hopes and at the relational level related to their family functioning.